2021
DOI: 10.1186/s12889-020-10145-1
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of self-medication practices in the context of the COVID-19 outbreak in Togo

Abstract: Background To date, there is no effective treatment for COVID-19, which is a pandemic disease, caused by a novel coronavirus called SARS-CoV-2. In Togo, where four in five people practice self-medication, the absence of a cure for COVID-19 and the constant progression of the disease requires an assessment of self-medication patterns in the context of the pandemic. This study aimed to estimate the prevalence of self-medication to prevent COVID-19 and its associated factors in Lomé, Togo. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
96
4
10

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(159 citation statements)
references
References 31 publications
13
96
4
10
Order By: Relevance
“…When considering reasons behind the use of specific medications, the study in Peru showed that Paracetamol and ibuprofen were mostly used for the alleviation of symptoms like fatigue, fever, muscle pain and sore throat, while paracetamol and azithromycin were mainly used for cough, sneezing, nasal congestion and shortness of breath management. 7 showed a lower prevalence than the one observed by our results, but were comparable to the Peru study. 6 Of 955 participants, the overall prevalence of self-medication to prevent COVID-19 was 34.2%.…”
Section: Discussionsupporting
confidence: 86%
“…When considering reasons behind the use of specific medications, the study in Peru showed that Paracetamol and ibuprofen were mostly used for the alleviation of symptoms like fatigue, fever, muscle pain and sore throat, while paracetamol and azithromycin were mainly used for cough, sneezing, nasal congestion and shortness of breath management. 7 showed a lower prevalence than the one observed by our results, but were comparable to the Peru study. 6 Of 955 participants, the overall prevalence of self-medication to prevent COVID-19 was 34.2%.…”
Section: Discussionsupporting
confidence: 86%
“…Moreover, 57.3% of the study samples were married and 42.7% were single. Furthermore, 29.8% of the study participants were illiterate, 54.5% had an elementary education, and 15.7% had a high school diploma or higher. Besides, 31.3% of the study samples were retired, 21.6% were self-employed, and 47.3% were unemployed.…”
Section: Resultsmentioning
confidence: 99%
“…[12][13][14] In the early pandemic, changes of activity and waves of false information increased fear; therefore, mothers try to prevent from getting infected by practicing selfmedication. [30][31][32] The children's online learning increased their burden, especially for mothers with responsibilities such as nursing or working mothers. 33 Our study in 610…”
Section: Discussionmentioning
confidence: 99%